The reception of the Homeric hymns - Faulkner, Andrew; Vergados, Athanassios; Schwab, Andreas (Oxford University Press, 2016)
A collection of original essays exploring the reception of the Homeric hymns in the literature and scholarship of the first century BC and beyond, particularly texts and authors of the late Hellenistic, Imperial and Late Antique periods.